Strategy of Golongan Karya to be Winner in Election Year 1971-1997 - Nisa, Noviah Iffatun; Naim, Mohammad; Umamah, Nurul (History Education, University of Jember, 2017)
Golkar is a political organization that develops by Orde Baru. Golkar always to be a winner by elections in the Orde Baru Era. The power of political support victory golkar is military, bureaucracy, organization mass, and the government policies. Golkar always perform in general election and perlemen successive for six times elections, namely in 1971, 1977, 1982, 1987, 1992, and 1997. The government put officer AD loyal to Suharto to occupy office bureaucracy in government central and local. The government uses various ways to winning golkar in elections, one of them are approaching those of the lord through GUPPI that is the social organizations that engaged in islamic education. GUPPI plays an important role in islamic mass persuasion. The government’s policy also contributes in succession golkar election common in the new order era. The outcome of an election 1971, Golkar have 227 seats (62,80 %), election 1977 with the results of 62,11 % of the vote, in election 1982 golkar managed to seize 10 seats, election 1987 golkar have 73,16 % of the vote, election 1992 get the result 68,01 % of the vote, and the receipt of the votes in the election 1977 reached 74,51 %. Keywords: Strategy, Winning, Golongan Karya, and Election.